The effect of energy input on flotation kinetics in an oscillating grid flotation cell - Changunda, K (Centre for Minerals Research, 2015)
Energy is known to play an important role in particle-bubble contacting in flotation. This thesis investigates the effect of energy input (or agitation) on the flotation kinetics of quartz in a novel oscillating grid flotation cell. The effects of bubble size and particle size have been recognized as important variables affecting particle-bubble contacting in turbulent systems and are investigated in this thesis. The research work done in this thesis is a continuation of the work done by the Centre for Minerals Research by Deglon (1998) who investigated the effects of energy in a batch mechanical flotation cell. However, this system has a very complex hydrodynamic environment, resulting from the large disparities in turbulence intensity. Previously Breytenbach (1995) had constructed a hybrid flotation column cell, which was essentially a column flotation cell that could be modified into a Jameson cell or a mechanically agitated column cell. He used this to compare particle collection efficiency in these different particle-bubble contacting environments. The third phase of the work was the oscillating baffle column (OBC), a novel flotation column that attains agitation by oscillating a set of orifice baffles through the slurry, thereby producing a more uniform shear rate distribution than would be obtained in an impeller driven system (Anderson, 2008). The OBC unfortunately has significant oscillatory flow and has high shear rates, which often result in detachment effects becoming appreciable. Oscillating grids generate near ideal hydrodynamic environments, characterised by turbulence that is relatively homogeneous and isotropic. The oscillating grid flotation cell used in this study was based on the oscillatory multi-grid mixer used by Bache and Rasool (2001). The oscillatory multi-grid mixer was purchased from these authors and retrofitted to produce the oscillating grid flotation cell. The novel oscillating grid cell consists of a 10 litre tank agitated by 19 grids with a mesh size of 8 mm and grid spacing of 18 mm. The grids were oscillated at a fixed amplitude, equal to the grid spacing, and over a range of frequencies, using a variable speed drive. Frother was added at 100 ppm to be consistent with the work of Deglon (2002) and Ahmed and Jameson (1985). A low gas flow-rate (100 ml/min) and solids concentration were specifically chosen in order that there was minimal influence on the structure of turbulence in the oscillating grid cell, as Bache and Rasool (2001) took measurements in water. Flotation tests were performed on methylated quartz particles (P80 = 100 μm) over a range of power intensities (0.015–0.60 W/kg) and using three different bubble sizes, generated by sintered glass discs (0.13, 0.24 and 0.82 mm). The flotation rate constant was found to increase approximately linearly with increasing particle size for all three bubble sizes. This was due to the increased probability of collision for larger particles and is well established in the flotation literature. A number of researchers have found that the flotation rate constant for quartz particles increases almost linearly with particle size, at low power intensities. An inverse power relationship was observed between bubble size and flotation rate constant for all fine, middling and coarse particle size ranges. This inverse power relationship was due to the increased probability of collision for smaller bubbles and is also well established in the flotation literature. More significantly, the flotation rate constant was found to increase almost linearly with increasing power intensity for all particle and bubble sizes used in this study. The majority of theoretical and experimental studies have found energy input to have less of an effect than the proportional/linear dependence observed in this study. In addition, the increase in the flotation rate constant with increasing power intensity was observed to depend on particle size, but to be less dependent on bubble size. These findings suggest that energy input and bubble size may respectively play more and less of a role in promoting particle-bubble contacting in turbulent environments than was noted in the flotation literature. However, a recent study by Newell and Grano (2006) done using a stirred tank also noted this linear dependence. Given the findings of this thesis, it is strongly recommended that further work be done to investigate the OGC at higher energy intensities (~3W/kg) and to scale it up so that it can be more comparable to the widely used mechanical flotation cells. The homogeneous and nearly isotropic turbulence generated by the OGC also makes it an ideal environment to characterize floatability for different ores.